Utilizing professional accounting concepts to understand and respond to academic dishonesty in accounting programs. (June 2019) - Bujaki, Merridee; Lento, Camillo; Sayed, Naqi
Highlights: The fraud triangle can help understand academic dishonesty from the perspective of professors. The pressure and attitude corner has elements of student and professor influence. Risk mapping reveals plagiarism and exam cheating as more impactful than assessment protocols. Professor efforts to control against academic dishonesty are mostly well-directed. Certain controls that are perceived to be effective are not used frequently by professors. Abstract: We apply professional accounting concepts to academic fraud in accounting education. First, we use the fraud triangle to understand professors' perceptions of academic dishonesty and find two components to each fraud triangle corner. Specifically, the attitude and pressure corners have elements of faculty and student agency, while the opportunity corner is within a professor's control. Second, risk mapping reveals plagiarism and exam cheating as more impactful than assessment protocols. We also find that faculty efforts to control academic dishonesty are mostly well-directed; however, there are opportunities to employ both preventive and detective controls more frequently.